Stability of tapioca chips fried in RBD palm olein treated with antioxidants - Augustin, M. A.; Berry, S. K. (Wiley, 1984)
The effectiveness of tertiarybutylhydroquinone (TBHQ), butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) in stabilizing tapioca chips was assessed by determining the peroxide and p-anisidine values, absorbances at 232 nm and 268 nm and the 18:2/16:0 ratios of oil extracted from tapioca chips. The order of effectiveness of the antioxidants in stabilizing the chips was found to be TBHQ > BHT > BHA. The order of effectiveness of antioxidants, TBHQ > BHT > BHA, was maintained for chips from corresponding 1st, 4th and 7th fryings. The loss of antioxidants during storage could not be directly related to oxidation parameters.